Therapeutic Communication Regarding Patient Anxiety in Orthopedic Surgical Services: An Exploration Study - Husain, Fadlyansyah Farid; Nuraryo, Imam (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
This research investigates the impact of therapeutic communication, particularly the way nurses can help pre-major surgical patients in the ward feel less anxious by giving them pre-surgical information. It is hoped that this essay would have a major positive impact on patients, families, medical facilities, and educational institutions. Offering preoperative patients’ therapeutic conversation is one way to lower their anxiety levels. This is predicated of nursing care, which emphasizes the patient, the nurse, and the interaction process that develops a relationship between the two. The goal of therapeutic communication is to support the client's healing process. It has been argued that therapeutic communication is a client-centered procedure that nurses use with a purposeful, intentionally designed approach. It is necessary for nurses to communicate with patients in a variety of scenarios. The research investigates first the conversations between nurses and clients on the objectives, outcomes, and procedures of surgery at one hospital in Jakarta. Second, anxiety: worry experienced by patients with femur fractures prior to significant surgery. This research uses secondary data analysis collected from various relevant research. This was the most common level of anxiety experienced by men. Male informants were more nervous than female informants. In addition, before and after receiving pre-surgical information, there was a difference in the degree of anxiety. There was a reduction in anxiety from a moderate level to a mild one.